Male gender, Charnley class C, and severity of bone defects predict the risk for aseptic loosening in the cup of ABG I hip arthroplasty - Lostak Jiri; Zapletalova Jana; Havranek Vitezslav; Gallo Jiri (BMC Musculoskeletal Disorders, 2010)
Abstract Background We studied which factor could predict aseptic loosening in ABG I hip prosthesis with hydroxyapatite coating. Aseptic loosening and periprosthetic osteolysis are believed to be caused, at least in part, by increased polyethylene (PE) wear rate via particle disease. Based on it, increased PE wear rate should be associated with aseptic loosening regardless of the type of implant. Methods We analyzed data from 155 revisions of ABG I hip prostheses to examine the influence of patient, implant, surgery, and wear related factors on the rate of aseptic loosening at the site of the cup. This was calculated by stepwise logistic regression analysis. The stability of the implant and severity of bone defects were evaluated intraoperatively. Results We found that men (odds ratio, OR = 5.6; p = 0.004), patients with Charnley class C (OR = 6.71; p = 0.013), those having more severe acetabular bone defects (OR = 4 for each degree of severity; p = 0.002), and longer time to revision surgery (OR = 1.51 for each additional year; p = 0.012) had a greater chance of aseptic loosening of the cup. However, aseptic loosening was not directly predicted by polyethylene wear rate in our patients. Conclusion Severity of bone defects predicts the risk for aseptic loosening in ABG I cup. Factors potentially associated with the quality of bone bed and biomechanics of the hip might influence on the risk of aseptic loosening in this implant.